Efektivitas berbagai program upaya pendidikan kesehatan gigi dan mulut pada sekolah dasar (Laporan Penelitian) - Tiarma Talenta Theresia; Asyurati Asia; Jonathan Steven (Jurnal Kedokteran Gigi Terpadu, 2022)
A school is a strategic place to be used as a target in dental and oral health programs. Objective: This scoping review examines the effectiveness of various school dental health business programs and primary school-based dental and oral health education. Method: Library Search uses PRISMA guidelines for 2016- to 2022 publications retrieved from the Pubmed database. A total of three reviewers conducted a library selection. Results: A total of 10 articles were analyzed, and various interventions were obtained in the program of promotive and preventive efforts for dental and oral health in elementary schools. Conclusion: Promotive and preventive efforts in the primary school environment need to be collaborated by involving the roles of teachers, parents, and peer cadres. Media use in dental and oral health education must also be adjusted to school conditions, so education can run optimally.